1991
DOI: 10.1111/j.1532-5415.1991.tb02897.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Behavioral Assessment Scale for Geriatric Out‐ and In‐Patients: the NOSGER (Nurses' Observation Scale for Geriatric Patients)

Abstract: Although a great number of psychometric tests and rating scales for the assessment of psychogeriatric patients is available, there is still an urgent need, in research and practice, for a clinical rating instrument that meets the following main requirements: (1) applicable to institutionalized and community patients and covering a wide range of behavioral pathology; (2) acceptable and easy to use for professionals and lay persons alike; (3) covering a wide range of behavior relevant to daily functioning but in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0
12

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(127 citation statements)
references
References 14 publications
1
112
0
12
Order By: Relevance
“…Two studies consistently had the highest mean distress rating across each of the behavior domains: Balieiro et al (2010) and Tan et al (2005). Both of these studies were clinic-based, higher distress ratings would be expected as those experiencing more BPSD might be more likely to attend a clinic, as, indeed, were the majority of studies included in the meta-analysis.…”
Section: Potential Explanations For Variability In Caregiver Well-beingmentioning
confidence: 96%
See 3 more Smart Citations
“…Two studies consistently had the highest mean distress rating across each of the behavior domains: Balieiro et al (2010) and Tan et al (2005). Both of these studies were clinic-based, higher distress ratings would be expected as those experiencing more BPSD might be more likely to attend a clinic, as, indeed, were the majority of studies included in the meta-analysis.…”
Section: Potential Explanations For Variability In Caregiver Well-beingmentioning
confidence: 96%
“…Both of these studies were clinic-based, higher distress ratings would be expected as those experiencing more BPSD might be more likely to attend a clinic, as, indeed, were the majority of studies included in the meta-analysis. It may be possible that dementia severity is an explanation, since participants in the studies with the highest distress scores (Tan et al, 2005;Balieiro et al, 2010) had moderate and severe dementia respectively, whereas Baiyewu et al (2003), who consistently reported the lowest distress scores across each of the behavior domains, included participants with mild dementia. However, both Aarsland et al (2007) and de Vugt et al (2006) reported lower mean distress scores in comparison with the other included studies, and they both included participants with moderate dementia.…”
Section: Potential Explanations For Variability In Caregiver Well-beingmentioning
confidence: 99%
See 2 more Smart Citations
“…These are the Neuropsychiatric Inventory (NPI), 236 Brief Psychiatric Rating Scale (BPRS), 229 Alzheimer's Disease Assessment Scale-Non Cognitive scale (ADAS-Noncog), 174 CERAD's Behavioural Rating Scale for Dementia, 231 the Revised Memory and Behaviour Problems Checklist, 247 Dysfunctional Behaviour Rating Instrument, 234 Behavioural Pathology in Alzheimer's Disease (BEHAVE-AD), 450 Nurses' Observation Scale for Geriatric Patients 243 and Plutchik Geriatric Rating Scale. 246 …”
Section: Consensus Conferencementioning
confidence: 99%